A Controlled Clinical Study on Efficacy of Siddha Varmam Therapy and Energy Sessions in the Management of Plantar Fasciitis - Sindhuja, Bhuvanagiri Sathya; Sankar, Injarapu; Reddy, Ram M; Tiwari, Shweta (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Background: Plantar Fascitis (PF) is one of the most common causes of heel pain, clinically presenting with intense discomfort, particularly during the initial steps taken in the morning. In the Siddha medical system, PF correlates symptomatically with Kuthikaal Vatham. It is frequently observed in individuals with obesity, those engaged in prolonged standing occupations, or following trauma to the heel region. Chronic cases often persist for several months and significantly impair daily activities. Aim: This study examines the effects of Siddha therapy with energy sessions on the PF patients in comparison to patients who are on NSAID’s with respect to pain reduction, mobility and functionality. Methods: A randomised comparative clinical study was conducted at the outpatient department of Chakrasiddh. A total of 40 patients aged between 18 and 50 years with clinically diagnosed Plantar Fasciitis were enrolled and randomly allocated into two groups (n=20 each). Group A (Experimental Group) received Siddha Varmam therapy integrated with Marma Chikitsa (energy healing sessions), and Group B (Control Group) was subjected to standard conservative treatment comprising non-steroidal anti-inflammatory drugs (NSAIDs) for 18 days. Outcome measures included the Visual Analogue Scale (VAS) for pain intensity and the Functional Foot Index (FFI) for mobility and functional assessment. Both groups were evaluated pre- and post-intervention. Statistical analysis was performed using paired and independent t-tests, with a significance level set at p<0.05. Results: Both groups demonstrated symptom relief post-intervention; however, Group A exhibited significantly greater improvement in pain reduction, mobility, and functionality. No recurrence of pain was reported in the experimental group at the follow-up stage. Comparative analysis revealed highly significant differences in VAS (t=11.35) and FFI scores (t=21.85) in Group A compared to Group B (p<0.05). Conclusion: Siddha Varmam therapy combined with energy healing significantly improved clinical outcomes in patients with Plantar Fasciitis. The study establishes this integrative approach as a safe, cost-effective, and non-invasive alternative to conventional conservative management. The results support the potential of Siddha-based interventions as holistic therapies in musculoskeletal disorders such as Plantar Fasciitis.